Benefits of Flipped Learning in Teaching ESP. - Tonenchuk, Tetiana; Tsyntar, Natalia; Mudra, Olena (Видавничий дім “Гельветика”, 2023)
This article explores the application of Flipped Classroom approach in the context of teaching English for Specific Purposes. The study uncovers the reasons of the already gained popularity of the approach, prioritizing active personalized learning over passive content consumption, it also dwells on the origins, foundations and essential aspects of the flipped classroom methodology. The research emphasizes efficiency of the approach in enhancing teaching and learning English for Specific Purposes. The specifics and common characteristics of the FlippedClassroom approach are determined, benefits andkey elements of the methodology are stated and analyzed. As revealed, this methodology can serve as a framework for fostering active engagement, critical thinking, and collaborative learning among students. The shift of traditional content delivery outside the classroom boosts valuable in-class time, enabling teachers to focus on in-depth comprehension, practical application, and skill development. The article also considers the importance of clear learning objectives, elaborate 386pre-class content, and interactive in-class activities. This paper delves into the specifics of implementing the flipped classroom, identifying its key components and mechanisms. The stages of planning an ESP (English for Specific Purposes) taskfor a flipped classroom are determined and illustrated. Furthermore, and examples of outcomes (learning objectives) for the task aimed to enhance job-related communication skills for IT students, possible pre-class, in-class and post-class task planning to ensure the achievement of the specified outcomes are provided. This investigation underlines the potential of the flipped classroom as on innovative teaching methodology tailored to the demands of English for Specific Purposes education, where practitioners are equipped with instruments to enhance their teaching practices and optimize student learning outcomes.
Keywords: flipped classroom; personalized learning; higher cognitive skills; learning objectives